2002
DOI: 10.1172/jci15417
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the MEF2 transcription factor in skeletal muscles from myotonic mice

Abstract: Becker syndrome, a recessive nondystrophic myotonia caused by mutations in the chloride channel 1 gene (CLCN1), is characterized by delayed muscle relaxation after contraction. The ADR (arrested development of righting response) mouse is an animal model for Becker syndrome. Skeletal muscles from ADR myotonic animals show an increased number of oxidative fibers with a lack of glycolytic fibers as well as signs of muscle hypertrophy. Through breeding ADR myotonic mice with mice harboring a MEF2-dependent reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…A similar change in fiber type composition can be seen in experimental mice affected with myotonia (29), which is a hallmark of DM1. Elevation of MEF2A in CUGBP1 transgenic mice is consistent with recent data from Dr. Olson's laboratory indicating that MEF2 activity is elevated in slow fibers in mouse muscles with myotonia (29). In these myotonic mice, ϳ80% of fibers are oxidative or slow.…”
Section: Discussionsupporting
confidence: 62%
“…A similar change in fiber type composition can be seen in experimental mice affected with myotonia (29), which is a hallmark of DM1. Elevation of MEF2A in CUGBP1 transgenic mice is consistent with recent data from Dr. Olson's laboratory indicating that MEF2 activity is elevated in slow fibers in mouse muscles with myotonia (29). In these myotonic mice, ϳ80% of fibers are oxidative or slow.…”
Section: Discussionsupporting
confidence: 62%
“…This could suggest that MEF-2 is DNA bound in the basal state. Furthermore, Wu and Olson (48) found that p38 activation is associated with enhanced MEF-2 transcriptional activity, without changes in MEF-2 DNA-binding activity. Additionally, others imply that MEF-2 DNA binding is a function of the abundance of the MEF-2 protein (7).…”
Section: Discussionmentioning
confidence: 98%
“…Other pathways involve calcium-sensitive proteins including calcineurin, which activates MEF2 by direct dephosphorylation (32) and Ca 2ϩ -calmodulindependent protein kinase, which activates MEF2 by alleviating the repression imposed by the histone deacetylases (HDACs) (51)(52)(53). Signaling via Ca 2ϩ -dependent pathways has recently been proposed as a potential means of fiber-type adaptation because sustained patterns of nerve stimulation elevate intracellular calcium levels (20), and recent experiments in mice support this hypothesis (31,54). Additionally, the transcriptional co-activator PGC-1␣ has been found to elicit slow fiberspecific gene expression, as well as mitochondrial biogenesis, through interaction with MEF2 (30).…”
Section: Discussionmentioning
confidence: 99%